2011
DOI: 10.18267/j.pep.398
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Predictions in International Financial Management by Enhanced GMDH Algorithm

Abstract: Abstract:Exchange rate forecasting is an important fi nancial problem that is receiving increasing attention nowadays especially because of its diffi culty and host of practical applications in globalising world of today. The paper presents an enhanced MIA-GMDH-type network, discusses its design methodology and carries out some numerical experiments in the fi eld of exchange rate forecasting. The method presented in this paper is an enhancement of self-organizing polynomial Group Method of Data Handling (GMDH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
(7 reference statements)
0
4
0
1
Order By: Relevance
“…In previous research by [21] and [24], it was shown that using several neuron architectures (or transfer functions) within a model produced better results than the model which only use one. Nevertheless, increasing the number of transfer functions in a model will increase the model's complexity.…”
Section: Proposed Combined Methodsmentioning
confidence: 99%
“…In previous research by [21] and [24], it was shown that using several neuron architectures (or transfer functions) within a model produced better results than the model which only use one. Nevertheless, increasing the number of transfer functions in a model will increase the model's complexity.…”
Section: Proposed Combined Methodsmentioning
confidence: 99%
“…Ivanova and Vojtovic (2016) and Taušer, Arltová, and Žamberský (2015) contend that due to the emergence of new technologies, it is expected to improve the temperature, humidity and other measurable and controllable working conditions affecting workplace comfort. According to Sadílek and Zadražilová (2016) and Taušer and Buryan (2011), the crucial issues also will be the safety improvement using rapid detection and increased protection in case of accidents, detection of gases, harmful radiation, fire hazards, including fire prevention and its effective automated disposal. Cepel, Belas, Rozsa, and Strnad (2019) and Jiránková (2012) insist that the possibilities for communication and cooperation will change completely, with an increasing emphasis on ergonomics, emissions reduction, and environment protection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stuchlíková zkoumá specifi ka hospodářských cyklů Japonska (Stuchlíková, 2011). Posílení praktického zaměření oboru v posledních letech pak lze demonstrovat na pracích zaměřených na efektivní řízení devizových expozic s využitím algoritmů umělé inteligence (Buryan, Taušer, 2008;Taušer, Buryan 2011) nebo výzkumu spotře-bitelského chování s ohledem na zemi původu v podmínkách ekonomické krize (Křečková, Odehnalová a Reardon, 2012).…”
Section: Období Po Roce 1989unclassified